Courses design based on perspective human-centered learning design - Taopik Barkah; Asep Herry Hernawan; Angga Hadiapurwa (Curricula: Journal of Curriculum Development, 2024)
This article aims to investigate and analyze course design based on a human-centered learning design perspective. In the modern educational era, effective course design requires an approach that understands the needs and characteristics of learners. The design of human-centered learning places learners at the center of the subject, acknowledging their diversity in learning styles, backgrounds, and individual needs. This research was conducted using the scientific literature review method to find data on the flow and recommendation model that can be applied in the development of courses or training with human-centered learning design. The results of this literature review provide insight into the principles of human-centered learning design and provide practical guidance for teachers, curriculum designers, and education practitioners in designing effective and impactful learning experiences. By understanding and applying this approach, it is expected that the development of learning design, both course development, learning materials, modules, and learning media can be more relevant, and interesting, and make a significant contribution to the development of the learning needs of today's students.   Abstrak Artikel ini bertujuan untuk menyelidiki dan menganalisis desain kursus berdasarkan perspektif desain pembelajaran yang berpusat pada manusia. Dalam era pendidikan modern, desain kursus yang efektif memerlukan pendekatan yang memahami kebutuhan dan karakteristik peserta didik. Desain pembelajaran yang berpusat pada manusia menempatkan peserta didik sebagai subjek utama, mengakui keberagaman mereka dalam gaya belajar, latar belakang, dan kebutuhan individual. Penelitian ini dilakukan menggunakan metode kajian literatur ilmiah untuk mencari data mengenai alur dan model rekomendasi yang dapat diterapkan dalam pengembangan kursus atau pelatihan dengan desain pembelajaran yang berpusat pada manusia. Hasil kajian literatur ini memberikan wawasan tentang prinsip-prinsip desain pembelajaran yang berpusat pada manusia dan memberikan panduan praktis bagi para pengajar, desainer kurikulum, dan praktisi pendidikan dalam merancang pengalaman pembelajaran yang efektif dan berdampak positif. Dengan memahami dan menerapkan pendekatan ini, diharapkan pengembangan desain pembelajaran baik itu pengembangan kursus, bahan ajar materi, modul, dan media pembelajaran agar dapat menjadi lebih relevan, menarik, dan memberikan kontribusi yang signifikan terhadap perkembangan kebutuhan belajar pelajar saat ini. Kata Kunci: berpusat pada manusia; desain berpikir; desain pembelajaran